Enacting spiritual leadership in business through ego-transcendence. Issue 1 (7th March 2016) - Klaus, Lauren; Fernando, Mario
Abstract : Purpose: – By applying Parameshwar's (2005) ego-transcendence model to two influential business leaders, the purpose of this paper is to examine how social innovation is promoted by business leaders through spiritual leadership. Design/methodology/approach: – The study used research tactics available within a phenomenological framework. Findings: – Based on the analysis of the two business leader case studies, several links between spiritual leadership and social innovation were identified. The central role of a higher purpose in enacting spiritual leadership as well as bringing about social innovation was most significant. Research limitations/implications: – Use of secondary data, the inherent weaknesses in analysis based on a single individual's interpretations and the analysis of only two business leaders were key limitations. A unique overlap was found between Dawson and Daniel's (2010) social innovation model and Parameshwar's (2005) ego-transcendence model. Practical implications: – As higher purpose was a key element in enacting spiritual leadership, leaders could look for the seeds of a higher purpose within the challenging circumstances of a situation. By shaping one's behaviour to a higher purpose-related social cause than merely following rules and procedures or social conventions, leaders are more likely to develop their own personal decision-making style. By highlighting the importance of paying attention to the suffering of others rather one's own suffering, the study also have implications for reducing the ego-based practices in day to day leadership in organisations. Originality/value: – Ego-transcendence model explains the link between social innovation and spiritual leadership in a non-organisational setting. The current study applies this link to the leadership context in business.